RESONANT ACOUSTIC EFFECT ON EXTRACTION OF BIRCH INNER BARK WITH ALKALI SOLUTION - Bobkova, Elena Olegovna; Kostukevich, Nataliya Garrievna; Ведерников, Дмитрий Николаевич (Химия растительного сырья, 2019)
The article describes the option of intensification extraction process from the birch inner bark. The influence of acoustic action (tensile-pulse modulation) on an increase in the yield of extractive substances on an aqueous solution of alkali (1% NaOH) is discussed. The extraction results were evaluated by the solid residue, the optical density of the solution, and the content of tannins. The yield of extractive substances is increased in 1.5 time with the help of a certain generator signal (meander) with a certain frequency (in the range of 170–190 kHz) and amplitude (2.7–2.9 V). The acoustic effect makes it possible to increase the yield of extractive substances by 17% if compared with the yield with mechanical stirring. The purity of tannin can be improved by adding ethyl alcohol to the extractant. The effect of background regulation with signal power less than 1.5 mW, exceeds the effect of mechanical mixing. A meander has the greatest effect in a series of electromagnetic signals: a meander, a sine, a triangle, a rectangle. The extraction time is determined. All counterparts taken into consideration the effect occurs. The cause of this phenomenon is examined. An explanation of the results is given.